DETERMINATION OF VISIT PATIENTS OF HYPERTENSION PANDEMIC PERIOD AT BRAWIJAYA UNIVERSITY HOSPITAL PATIENT VISITS OF HYPERTENSION IN PANDEMIC PERIOD - Andarini, Sri; Hanggara, Dian Sukma; Setijowati, Nanik (Universitas Brawijaya, 2023)
The World Health Organization (WHO) estimates a continuous increase in the number of hypertension cases alongside the expanding population. It is projected that approximately 29%, or around 1.6 billion people worldwide, will be afflicted with hypertension by 2025. The findings of the 2018 Riskesdas survey reveal a prevalence of hypertension in the population aged > 18 years based on national measurements, standing at 34.11%. This represents a 9% surge from the 2013 Riskesdas data, which recorded a prevalence of 25.8%. East Java Province ranks seventh with a prevalence rate of 36.32%, surpassing the national average. In the pursuit of hypertension control, it has been integrated into the Preventive Efforts of the Healthy Indonesia Family Approach Programs (PIS-PK) under point 7, mandating continuous monitoring of hypertension status for family members with a history of hypertension. This study aims to identify determinant factors associated with enhanced services and visits for hypertension patients at Universitas Brawijaya Hospital in Malang amidst the pandemic. This study employs an observational analytic design, aiming to analyze the relationship between education level and medication adherence among hypertension patients during the COVID-19 pandemic. Temporally, this research adopts a cross-sectional approach, where both dependent and independent variable data are collected simultaneously. The study was conducted at Brawijaya University Malang, utilizing data from hypertensive patients who visited the hospital between March 2020 and March 2022. Logistic regression analysis with α = 0.05 will be employed for analytical purposes. The variable most strongly associated with hypertension patient visits is insurance ownership, exhibiting a Chi-Square value of 26.716. Additionally, the age variable demonstrates a correlation with patient visits, with a Chi-Square value of 4.312. The corresponding P-values for insurance ownership (p = 0.000) and age (p = 0.038) indicate a significant relationship between insurance ownership, age, and patients' motivation to seek healthcare. The determinant factors that positively influence hypertensive patient visits during the pandemic at Brawijaya University Hospital are insurance ownership and age. On the other hand, gender, regional affordability, and occupation exert a lesser impact on patient visits.